*Ir4+ ion‐free 12CaO·7Al2O3 single crystal grown by the CZ method. Issue 8 (31st July 2013) - Sun, Jinchao; Xu, Yanling; Wang, Rui; Liu, Xinrong; Qu, Yunfei
<x xml:space="preserve">Abstract</x> Ir4+ ions‐free 12CaO7Al2O3 (C12A7) single crystals which was colorless and transparent have been grown by CZ method under 0.5% oxygen containing nitrogen atmospheres for the first time. Powder X‐ray diffraction pattern and X‐ray single crystal diffraction were used to investigate the micro structure and quality of C12A7 single crystal. Results show that the crystal was C12A7 single crystal with tetragonal symmetry. The contents of Ir4+ in C12A7 single crystal was tested by ICP along with visible light transmittance. There was no Ir4+ in C12A7 crystal grown in 0.5% oxygen containing nitrogen atmospheres. Contents of Ir4+ in … <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>